2005
DOI: 10.1038/sj.npp.1300651
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Tryptophan Depletion on Negative Symptoms and Smoking Topography in Nicotine-Dependent Schizophrenics and Nonpsychiatric Controls

Abstract: We studied the effect of acute tryptophan depletion (ATD), which transiently reduces brain serotonin, on negative symptoms and cigarette smoking topography in schizophrenic smokers. Nicotine-dependent schizophrenics (n ¼ 11) and nonpsychiatric controls (n ¼ 8) were examined after ingesting comparable mixtures that do and do not deplete plasma tryptophan. Tryptophan-depleting and placebo mixtures were administered double-blind and in counterbalanced order. Conditions were separated by a 1-week interval. Psychop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
8
1
Order By: Relevance
“…Acute tryptophan depletion, which transiently decreases brain serotonin, has been shown to intensify smoking behaviour in non-depressed individuals (Hitsman et al 2005), and a role for serotonin systems in the inhibitory control of behaviour has been established (Olausson et al 2002). Furthermore, manipulation of brain serotonin via administration of SSRIs is known to improve nicotine abstinence rates (Hitsman et al 1999) and reduce some of the symptoms of withdrawal in participants with a history of major depression (Covey et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Acute tryptophan depletion, which transiently decreases brain serotonin, has been shown to intensify smoking behaviour in non-depressed individuals (Hitsman et al 2005), and a role for serotonin systems in the inhibitory control of behaviour has been established (Olausson et al 2002). Furthermore, manipulation of brain serotonin via administration of SSRIs is known to improve nicotine abstinence rates (Hitsman et al 1999) and reduce some of the symptoms of withdrawal in participants with a history of major depression (Covey et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, persons with schizophrenia have an increased risk of initiation of daily smoking (Zhang et al 2010). Smokers with schizophrenia are often highly nicotine dependent, and studies have reported greater carbon monoxide boost, puffs, puffs per cigarette, and increased saliva cotinine concentrations in smokers with schizophrenia as opposed to smokers without schizophrenia (Hitsman et al 2005, Strand et al 2005; Tidey et al 2005, Williams et al 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Results provide further human experimental evidence suggesting that serotonin is involved in the direct control of cigarette smoking behavior (Hitsman et al 2005), and also may play an important role in regulating cravingassociated processes. Tryptophan depletion has been previously shown to influence urge to drink alcohol among patients with alcohol dependence and MDD who had responded to serotonergic antidepressant treatment (Pierucci-Lagha et al 2004).…”
Section: Discussionmentioning
confidence: 95%
“…In a second experiment, Pergadia et al (2004) found that decreased bilateral cerebral blood flow to the inferior frontal lobe produced by ATD relative to placebo was associated with increased depressed mood among smokers. Finally, Hitsman et al (2005) observed that ATD influenced cigarette smoking topography in both nonpsychiatric and schizophrenic smokers. It is interesting to note that ATD had no effect on depressive symptoms in either group in that experiment, suggesting that its influence on intensifying smoking behavior was not mediated by acute changes in negative mood.…”
Section: Introductionmentioning
confidence: 90%